Spectroscopic Analysis of Tempeh Protein Content during the Production Process - Zul Arham; Kurniawan Kurniawan; Laode Anhusadar; Ismaun Ismaun (IAIN Kendari, 2021)
Tempeh is a local Indonesian food that is liked by the community, both locally and internationally. The high protein content is the reason for choosing tempeh as a complementary food. In its production, tempeh is made by two important processes, including treatment and fermentation. During this process, the protein can be damaged, resulting in a decrease in the protein content of tempeh. Based on these problems, this study aims to analyze the reduction of tempeh protein content during the production process. The analysis used two spectroscopic methods, including FTIR and UV-Visible. FTIR spectroscopy was used to observe the reduction in total protein content, while UV-Vis spectroscopy was used to observe the reduction in dissolved protein content. The results of the study for FTIR analysis showed that at the pretreatment and fermentation stages, both caused a decrease in the total protein content of tempeh. This was observed with a decrease in the intensity of IR absorption at a wavenumber of 1745 cm-1 which is identical to the C=O group and 1543 cm-1 which is identical to the N-H group. Based on the results of the UV-Visible study, it shows that the fermentation time affects the amount of dissolved protein. This situation is supported by the increasing pH of tempeh and decreasing water content during fermentation.